Early enteric and hepatic responses to ingestion of polystyrene nanospheres from water in C57BL/6 mice - Szule, Joseph A.; Curtis, Lawrence R.; Sharpton, Thomas J.; Löhr, Christiane V.; Brander, Susanne M.; Harper, Stacey L.; Pennington, Jamie M.; Hutton, Sara J.; Sieler, Michael J.; Kasschau, Kristin D. (Frontiers in Water, 2022)
Drinking water is one of numerous sources of human exposure to microscale and nanoscale plastic particles. Here, using a mouse model, we tested enteric and hepatic cellular responses to nanoplastic ingestion. At 1.5 or 25.5 hours after an oral dose of 70 mg polystyrene nanospheres (PSNS)/ kg (nominal diameters of 20 and 200 nm) in aqueous suspension female mice exhibit no overt signs of toxicity. Routine histopathology on small intestine and liver reveals no acute toxicity. Immunohistochemistry detects an increase in the number of enterocytes with cleaved caspase-3 (active form) after PSNS exposure (p≤0.05) indicating progression towards lytic cell death via a proinflammatory pathway. This is not evident in liver after PSNS exposure. Transmission electron microscopy detects lytic cell death in enterocytes at 25.5 hours after 200 nm PSNS exposure. Putative endosomes in liver appear to sequester 20 nm and 200 nm particles 25.5 hours after exposure. Both 20 nm and 200 nm PSNS appear in putative perinuclear autolysosomes 25.5 hours after treatment. No significant changes in gene expression in the small intestine or liver 25.5 hours were observed after dosing, but there was a trend towards altered expression of cyp1b1 in the liver. Analysis of the fecal microbiome shows loss of diversity after exposure to both 20 and 200 nm particles after 25.5 hours. Taken together, these results suggest risk from ingestion of nanoscale plastic particles from drinking water, which deserves systematic investigation.